Sarcoidosis Presenting as Granulomatous Mastitis, Erythema Nodosum, and Arthritis Syndrome: A Case Report and Comprehensive Review of the Literature - Aseel Abuhammad MD; Maram Albandak MD; Mohammed Ayyad MD; Arein Madia MD; Osama N. Dukmak MD; Laith Alamleh MD (SAGE Publishing, 2024)
Granulomatous mastitis (GM) is a long-term inflammatory disease of the breast that usually occurs in women of reproductive age. Autoimmune mastitis is one of the most common pathological breast conditions necessitating tailored treatment. However, GM as a first clinical manifestation of sarcoidosis is uncommon. Simultaneous occurrence of GM, erythema nodosum (EN), and arthritis, termed "GMENA" syndrome, is a rare clinical entity associated with autoimmune rheumatic diseases. Herein, we report the case of a 31-year-old female patient with GMENA syndrome, who presented with a painful nodule of the left breast. Initial treatment entailed antibiotics under the presumption of a breast abscess, yielding negligible improvement. During this period, the patient developed polyarthritis and bilateral EN on the lower extremities. Histopathologic examination of the breast tissue exhibited noncaseating granulomas. The patient responded positively to prednisolone and methotrexate treatment. Literature review revealed a coherent pattern across GMENA cases. Our findings suggest that the "GMENA" syndrome represents a unique acute manifestation of sarcoidosis and highlight the necessity for heightened awareness, accurate diagnosis, and tailored therapeutic approaches for GMENA syndrome. Further research is warranted to elucidate its cause and optimize patient management. This case highlights the importance of identifying and effectively managing such interrelated clinical presentations.